Malignant melanoma: sex differences in survival after evidence of distant metastasis. - Rampen, F. (Nature Publishing Group, 1980)
Survival data of 106 males and 110 females with disseminated malignant melanoma, recorded between 1956 and 1975, were reviewed. Survival after first evidence of distant metastasis was significantly longer in women than in men (P = 0.02). There was no difference in survival after occurrence of distant metastasis between pre- and postmenopausal women, nor between parous and nulliparous women. However, there was a clear female superiority of premenopausal women over males less than or equal to 50 years and, to a lesser extent, of postmenopausal women over males > 50 years. It is concluded that endocrine factors enhance melanoma activity in the male patient. The suggestion that malignant melanoma is "testosterone-dependent" seems justifiable. A possible explanation is given for the general experience that women with melanoma show a more favourable response to chemotherapy than men.